2006
DOI: 10.1038/sj.sc.3101900
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects of extract of Ginkgo biloba (EGb 761) on nerve cells after spinal cord injury in rats

Abstract: Study design: An experimental animal model was used to assess spinal cord injury following lateral hemitransection at thoracic spinal cord level. Objective: To determine whether extract of Ginkgo biloba (EGb) could have a neuroprotective effect in spinal cord injury (SCI) in rats. Setting: Department of Biological Sciences and Biotechnology, Tsinghua University, China. Methods: A total of 72 adult rats were divided randomly into three groups: the EGb group, normal saline (NS) group, and sham operation group (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…2009). Several in vivo experiments also showed that EGb761 protected spinal cord neurons after spinal ischemia‐reperfusion or injury (Ao et al. 2006; Mechirova et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009). Several in vivo experiments also showed that EGb761 protected spinal cord neurons after spinal ischemia‐reperfusion or injury (Ao et al. 2006; Mechirova et al.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that EGb761 protects spinal cord neurons from death induced by both injury insults in a dose-dependent manner, consistent with our previous report (Jiang et al 2009). Several in vivo experiments also showed that EGb761 protected spinal cord neurons after spinal ischemia-reperfusion or injury (Ao et al 2006;Mechirova et al 2009). EGb761 was also shown to reduce neuronal death in global brain ischemia and Glu-induced excitotoxicity (Chandrasekaran et al 2002), and inhibit NMDA receptor-mediated calcium influx and neuronal death (Szasz et al 2008;Shi et al 2010).…”
Section: Egb761 Protects Neurons From Glu and H 2 O 2 -Induced Cell Dmentioning
confidence: 98%
“…In addition, in lymphocytes isolated from spleen of aged mice treated with 100 mg/Kg EGb 761 for 2 weeks, less susceptibility to ROS-induced apoptosis was found [45]. In the peripheral nervous system, posttreatment with EGb 761 (100 mg/kg) decreased the number of apoptotic cells in injured rat spinal cord [46]. In central nervous system, treatment with EGb 761 (40 mg/kg) reduced neuronal death in the substantia nigra pars compacta from an experimental model of Parkinson's disease [47].…”
Section: Antiapoptotic Effects Of Egb 761mentioning
confidence: 99%
“…Furthermore, it has been reported that EGb has anticancer effects in breast and gallbladder cancers [ 11 , 12 ]. These effects potentially involve diverse mechanisms, including the reduction in the number of apoptotic cells [ 13 16 ], the maintenance of mitochondrial integrity [ 17 20 ], inhibition of cyt c release from mitochondria, induction of gene expression of the anti-apoptotic protein Bcl-2 [ 21 25 ], reduction in the gene expression of caspases [ 21 , 24 , 26 28 ] and DNA fragmentation [ 21 , 24 ]. In addition, EGb up-regulates the mRNA expression of antioxidant enzymes such as mitochondrial SOD, GPx, GCLC, and HO-1 to decrease oxidative tissue damage [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%